Strategies for Sustainable Water Management: Hydrochemical Profiling and Protection Zone Design in Rania Basin, Iraq - Salih, Ata O.; Al-Manmi, Diary A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Groundwater in the Rania basin, Iraqi Kurdistan region, has been under intensive exploitation in the last two decades, where quantity and quality are both affected. Hence, any attempt to protect the aquifers has become an urgent need. Saruchawa, Qulai Rania, and Qulai Kanimaran are the three large springs, among dozens of others in the area, that are heavily relied on as the sole or main source of water supply. Hydrochemical analysis, the first and most practical step to evaluating the water quality, was carried out through 60 water samples collected from 13 springs and 17 wells in both dry and wet seasons (October 2018 and May 2019). Laboratory results show a high calcium bicarbonate concentration with weak acids’ dominance. Protection zones are delineated for these springs using aquifer susceptibility to contamination and analysis of the recession part of the spring curves. The equivalent relationship between the protection factor (Fp) produced by the Epikarst, protective cover, infiltration condition, and Karst network development mapping method and the groundwater protection zone (S) is considered. Qulai Rania and Kanimaran Springs are mapped to be in S2 (a highly vulnerable area), whereas Saruchawa Spring is located in S1 (very highly vulnerable). Based on the second method results (recession curve analyses), all three selected springs fall under the (D-type) vulnerability category. As a result, the immediate protection zone was going to be surrounded by the inner protection zone, and both are enclosed within the outer protection zone, which covers the remainder of the catchment area.